Gas supply control and experimental validation for polymer electrolyte membrane fuel cells. (May 2023) - Li, Cheng; Zhao, Honghui; Liu, Huayang; Jiang, Weihai; Ding, Tianwei; Gao, Bingzhao; Gao, Jinwu
Abstract: Gas supply system control, which consists of air and hydrogen supply control, are two basic and crucial topics for proton exchange membrane fuel cell (PEMFC) control. To protect the PEM and improve the performance of the PEMFCs, the air pressure and flow of the cathode, and the hydrogen pressure of the anode should be precisely controlled. In this paper, we primarily research the modelling of the cathode and anode and the nonlinear controller design for pressure control, as well as air flow control. In detail, control-oriented models are established for cathode and anode controller design. Owing to the existence of model uncertainty and disturbances, such as humidity, temperature, and water vapour, an extended state observer (ESO) is designed to estimate and compensate for these influences. Cathode and anode pressure controls are synthesized in the uniform control scheme. For air flow control, a feedforward channel based on the air flow model of the compressor and a feedback channel based on the proportional–integral (PI) controller are proposed to regulate air flow. The proposed control methods are validated by experiments under different operating conditions of PEMFCs. Highlights: The proposed method can regulate gas flow and pressure to the desired set point. The simple model can be used for controller design by the compensation technique. The strategy is well validated by experiments to show its promising potentials.